Inclusive Music Education: Strategies and Challenges in Teaching Music Lessons With a Student With Autism Spectrum Disorder Present in the Classroom - Marinšek, Miha; Hmelak , Maja (Interdisciplinary Research in Teaching and Learning: New Perspectives and Approaches, 2024)
This study investigated musical methods of teaching and learning, forms of teaching, adaptations (school, classroom and lesson adaptations), and challenges faced by elementary school teachers when instructing music lessons in the presence of a student with autism spectrum disorder (ASD) in a mainstream classroom. Employing a mixed methods design, the research utilized a questionnaire and semi-structured interviews with a focus on eight key research questions, exploring teacher challenges, the impact of training and experience, collaboration with support networks, and teacher competencies in addressing the needs of students with ASD in music lessons. The findings underscore the need for specialized training and resources to both enhance inclusive education and effectively engage students with ASD in music lessons in the mainstream elementary classroom.